2017
DOI: 10.1002/nha3.20197
|View full text |Cite
|
Sign up to set email alerts
|

Building Blocks of Contemporary HRD Research: A Citation Analysis on Human Resource Development Quarterly between 2007 and 2013

Abstract: Human resource development is known to encapsulate a collection of social science disciplines including communications, psychology, and economics. Since these and other similar areas are the cornerstones of HRD, the changing nature of HRD demands constant reflections on the value and building blocks of contemporary HRD inquiries. This article presents a citation analysis of articles published in Human Resource Development Quarterly from 2007 to 2013 to provide an overview of the various disciplines contributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Employees' career development is seen as one of the topics central to HRD (Park and Rothwell 2009;Mehdiabadi et al 2017;Shuck et al 2018). That is, as the range of possible occupational and educational choices in Western societies has increased dramatically (OECD 2011), employees are expected to engage in lifelong learning in order to stay broadly employable (Baruch, Szűcs, and Gunz 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Employees' career development is seen as one of the topics central to HRD (Park and Rothwell 2009;Mehdiabadi et al 2017;Shuck et al 2018). That is, as the range of possible occupational and educational choices in Western societies has increased dramatically (OECD 2011), employees are expected to engage in lifelong learning in order to stay broadly employable (Baruch, Szűcs, and Gunz 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al, 2013). More recently, Hedayati et al (2017) identified disciplines that have contributed to contemporary HRD research through citation analysis of articles published in HRDQ from 2007 to 2013. Analysis of 5807 citations showed that psychology remains a prominent building block for current HRD research, while the presence of economics and systems theory is less evident.…”
Section: Citation Analysis Of Hrdmentioning
confidence: 99%
“…Over the years, HRD researchers have made a consistent effort to capture a panoramic view and dynamic nature of HRD scholarship (e.g., Jeung, Yoon, Park, & Jo, 2011; Mehdiabadi, Seo, Huang, & Han, 2017; Ruona, Lynham, & Chermack, 2003; Sleezer & Sleezer, 1998; Sun & Wang, 2013; Torraco, 2005; van der Veen, 2006). Here, I highlight the two most recent and more inclusive efforts.…”
Section: Historical Trends: What Has Been Published In Hrd?mentioning
confidence: 99%